Innate Immunity in Health and Disease - Saxena, Shailendra K.; Prakash, Hridayesh (IntechOpen, 2021)
The book focuses on various aspects and properties of innate immunity, whose deep understanding is integral for safeguarding the human race from further loss of resources and economies due to innate immune response-mediated diseases. Throughout this book, we examine the individual mechanisms by which the innate immune response acts to protect the host from pathogenic infectious agents and other non-communicable diseases. Written by experts in the field, the volume discusses the significance of macrophages in infectious disease, tumor metabolism, and muscular disorders. Chapters cover such topics as the fate of differentiated macrophages and the molecular pathways that are important for the pathologic role of macrophages.